Epidemiology of the Zika virus - González Collantes, Sofía (2017)
The Zika virus was first isolated in a Rhesus monkey in the Zika forest in Uganda in 1947, during a study on the transmission of jungle yellow fever. In 2007, there was the first major outbreak of infection in the island of Yap in Micronesia; and by the end of 2013; an outbreak began in French Polynesia. In May 2015, native circulation in continental America (Brazil) was registered. To date, 47 countries / territories in the Americas have confirmed native cases of infection, in six departments in Peru. At the beginning of 2016, seven countries or territories reported an increase in the incidence of microcephaly after an outbreak of infection by the Zika virus. Worldwide, 23 countries or territories have reported cases of microcephaly and other malformations of the central nervous system possibly associated with Zika virus infection; and in the Andean Region, only Colombia has presented confirmed cases. In French Polynesia, during the 2013-2014 Zika outbreak, 42 cases of Guillain-Barré syndrome were identified, 88% of which had a clinical picture compatible with Zika virus infection. In early 2016, and in the context of the Zika virus infection outbreaks, Brazil, Colombia, El Salvador, Suriname and Venezuela reported an increase in cases of Guillain Barre’s syndrome.